The transition from school to post-secondary education - What factors affect educational decisions? - Katja Seidel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
This paper analyses the concrete post-school decision of school students whether to study or to enter the German VET system. It focuses on the investigation of individual risk preferences and the social background of individuals, and the effect on the ultimate decision to enrol in university or to start an apprenticeship, given the same level of qualification. For the empirical approach, the German SOEP is used, and information on individuals' educational decisions between 2007 and 2013 is considered. The results indicate that (i) individual risk preferences do not have an overall effect on the real transition and are not conditional on the academic background of parents; (ii) privileged individuals are more likely to take up higher education; and (iii) even when parents without an academic background support their children during school, they are less likely to guide their children into tertiary education.
Keywords: D81; I24; J24; 330; educational decision; risk preferences; uncertainty; social classes; family background